General string cosmologies at order α′3 - Codina, Tomas (2021)
We compute the cosmological reduction of general string theories, including bosonic, heterotic, and type II string theory to order α′3, i.e., with up to eight derivatives. To this end, we refine recently introduced methods that allow one to bring the reduced theory in one dimension to a canonical form with only first-order time derivatives. The resulting theories are compatible with a continuous O(d,d,R) invariance, which in turn fixes the B-field couplings.